Growth of Communicative Proficiency in Teaching Foreign Languages for Work-Related Objectives (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study investigates the effectiveness of a task-based approach to teaching foreign languages for work-related objectives, focusing on communicative proficiency development. This article suggests that the task-based approach effectively fosters work-related communicative proficiency, highlighting its potential to prepare students for success in a globalized workforce. Further research on this methodology across languages and professional fields is encouraged.